A review of construction work sampling methods and an investigation into their use in South Africa - Hund, Peter J (Department of Construction Economics and Management, 2017)
Work sampling had its origin in industrial engineering; however, its use in construction has increased greatly during the 1970's and 1980's. Research would suggest that most of the innovation in this field is taking place in the United States. The basic methods of Work Sampling have been developed to suit the peculiarities of the construction site as opposed to the production line or factory where it was first used. The objectives of this report are as follows: 1. To review the existing methods of Construction Work Sampling as well as discuss further aspects and problems which should be considered when undertaking a Work Sampling study. 2. To compare Construction Work Sampling with other methods of measuring productivity. 3. To evaluate by means of a case study the ease of applicability of the sampling methods to a South African construction site, and at the same time to identify differences between the description of the methods in theory and their use in practice. 4. To establish by means of a questionnaire the extent to which Construction Work Sampling methods are already in use in South Africa as well as other related information. Information for this report was obtained from journals, manuals, text books, interviews, and the case study and questionnaires mentioned.